Biological control on gastrointestinal nematodes in cattle with association of nematophagous fungi. Issue 12 (2nd December 2017) - Fernandes, Fernanda Mara; Aguiar, Anderson Rocha; Costa Silva, Laryssa Pinheiro; Senna, Thiago; Mello, Ingrid Ney Kramer de; Oliveira, Thais de; Freitas, Samuel Galvão; Ferreira Silveira, Wendeo; Braga, Fabio Ribeiro; Araújo, Jackson Victor
ABSTRACT: This study aimed to evaluate the efficacy of the association of the nematophagous fungi ( Duddingtonia flagr ans-AC001); ( Pochonia chlamydosporia -VC4) and ( Arthrobotrys robusta -I31) in a pelletised formulation of a sodium alginate matrix. The viability and activity of pellet germination and fungal activity (after encapsulation) were evaluated using in vitro and in vivo tests. Next, 12 heads of cattle, Dutch mestizo x zebu, with an average age of 12 months were dewormed with an anthelmintic. Next, 20 days after treatment with the anthelmintic, the animals were randomly divided into two groups of six animals each, and placed in two paddocks with 7.0 ha each of Brachiaria decumbens with historical grazing by animals naturally infected by gastrointestinal nematode parasites. At first, each animal was treated with 2 g of pellets per 10 kg of animal, containing the associated fungi (AC001 + VC4 + I31) administered twice a week in conjunction with commercial feed. Each animal in the control group received 2 g of pellets without mycelia added to the feed. The percentage reduction of infective larvae in the in vitro test was 94% ( p  < .01). In the in vivo test, the treated animals with fungal association had lower egg counts per gram of faeces ( p  < .01) compared to the control group animals – a reduction of 91.8%. The reduction in the number of infective larvae recovered from the pasture was 27.5% at a distance of 0–20 cm from the stool bulk, and 26.7% at a distance of 20–40 cm. This association (AC001 + VC4 + I31) of nematophagous fungi was effective in nematode control.